22PFeasibility of precision cancer medicine in advanced gynaecologic cancers. (7th November 2019) - Taghizadeh, H; Mader, R M; Müllauer, L; Aust, S; Polterauer, S; Reinthaller, A; Kölbl, H; Seebacher, V; Grimm, C; Prager, G
Abstract: Background: Advanced gynecologic cancers have a poor prognosis and constitute a major challenge for adequate treatment strategies. By analyzing and targeting molecular alterations, precision cancer medicine (PCM) may be a viable option for the treatment of advanced gynecologic cancers. Methods: In this single center, real-world retrospective analysis of our PCM platform, we describe the molecular profiling of 72 patients diagnosed with different types of metastasized BTC. Tumor samples of the patients were examined by a 162-gene next-generation sequencing (NGS) panel, immunohistochemistry (IHC), fluorescence in situ hybridization (FISH) and RNA fusion panel. Results: In total, we identified 209 molecular aberrations in 72 patients. The ten most frequently alterations were TP53 (n = 42), KRAS (n = 14), PIK3CA (n = 11), PIK3R1 (n = 9), ATR (n = 8), PTEN (n = 8), BRCA1 (n = 6), NF1 (n = 4), NOTCH1 (n = 4), POLE (n = 4) that make up together over half of the molecular alterations (52.6%). BRAF mutations and gene fusions each were observed in two patients. 21 patients were found to have only one mutation and 44 patients had more than one mutation. No mutations were detected in 7 patients. IHC detected expression of p-mTOR and EGFR in 58 and 53 patients, respectively. In over two-thirds (n = 51) of the 72 patients, a targeted therapy was suggested, based on the identified genetic mutations. The most frequently recommended specific treatment was the combination of everolimus with exemestan (n = 19). The median turnaround time from biopsy to discussion in our multidisciplinary tumor board was 20 days. The median turnaround time from biopsy to therapy initiation was 26 days. Conclusions: Based on our observations, it seems that PCM might be a feasible treatment approach for advanced gynecologic cancers with limited treatment options. Legal entity responsible for the study: Medical University of Vienna. Funding: Has not received any funding. Disclosure: H. Taghizadeh: Travel / Accommodation / Expenses: Roche. All other authors have declared no conflicts of interest.